O trabalho profissional dos Assistentes Sociais com os venezuelanos em situação de imigração e refúgio: os desafios na proteção social especial da Política de Assistência Social em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The professional work of the social worker developed in the social assistance policy, and given to Venezuelan immigrants and refugees, in the services of special protection host is the focus of this study, as well as, it was aimed to reveal the contributions of this work for the improvement and strengthening of special social protection in Manaus. The discussion was guided by the understanding that the social issue is present in the forced displacement of Venezuelans in a context of geopolitical domination and dependence. This displacement created a demand for the social assistance policy that structured its services to receive them. In Brazil, this policy is guided by the imperative of the 1988 Federal Constitution, which advocates that the social assistance right is guaranteed to those who need it, that is, immigrants and refugees from Venezuela are users of that policy. In relation to the methodological procedures of the research, it relied on the critical direction of the historical-dialectical method based on the analytical categories of historicity, totality and contradiction, in addition to the theoretical support of the categories of social issue, social assistance policy and professional work of the social worker. The research unfolded in the bibliographical, documentary and field survey modalities. Aside from this, six social service professionals were interviewed in order to learn about the actions offered to the Venezuelan public, the view of social workers in relation to the expressions of the social issue present in forced displacement and also to verify how professional work contributed to the improvement of special protection in the social assistance policy in Manaus. Not that it refers to the results of the study, initially there is an analysis aimed at apprehending the movement of Venezuela's removal from these themes, in which it seeks to unveil the hidden reality due to the superficiality of the means of communication for the which this problem is addressed. Note that the social issue is part of the imperialist game of interests that surrounds this country. In addition, I identify that, as a result of this recent displacement, it is the result of the globalization of capitalism and its daring maladies in ideological and spatial dominations. After this initial historical approach from Venezuela, the analysis of the Brazilian context of democratization of the post-Constitutional guidelines of 1988 and the reconstruction of direct socio-assistance, seeking to elucidate the structure and organization of the social assistance policy (documentary investigation), users, with an emphasis on reframing attention to needs arising from possible vicissitudes of life. And it turns out that the actions taken to meet the demands, which will arise from the relocation, are not intended to separate them or make them exclusive to this audience, as soon as the policy recommends: o respect the specificity / needs of two serious users. Therefore, it is worth mentioning that the social assistance policy, not the current situation, is being directed towards or from assistentialist and clientelist positions. During the year of work of the social worker, it is evident that a contradiction was made in view of the guarantees given in the legislation and regulations (specific to the profession and also referring to work in that policy) and the reality of the occupational field. Finally, it is the Social Assistants who work at SUAS who, despite the precarious process of their working conditions, will be able to provide guidelines in the area of carrying out their work and contribute to the strengthening of the special protection of the social assistance policy in Manaus.
Keywords: Assistentes sociais; Política de assistência social; Venezuelanos; Refugiados; Mundialização da capitalismo; CIÊNCIAS SOCIAIS APLICADAS; Questão Social; Trabalho Profissional do assistente social; Assistência Social; Migração; Refúgio